Desa Sebagai Unit Pemerintahan Terendah Di Kota Pariaman - Hengki Andora (Jurnal Ilmu Hukum, 2010)
Pariaman apply two system of lowest government inits region, namely the system of Desa and system ofKelurahan. Number of desa is 55 Desa and number ofKelurahan is 16 Kelurahan. Pariaman not want to applythe system of Nagari, with arguing: i) in ruralcommunities have felt comfortable with the system ofDesa (status quo); i) the establishment of Nagarigovernment system will cause a reduction in theallocation of development fund from the goverment;iii) Pariaman already heterogenous society; and iv)the establishment of Nagari system will cause losspublic office and employment for people who sit in theDesa institutional structures. Desa in Pariamanperformed in accordance with Local Regulation No. 7of 2007 on Desa. Institutional Desa consist of Desagovernment, Badan Permusyawaratan Desa (BPD),and another Desa Institutional.